2019
DOI: 10.5009/gnl18276
|View full text |Cite
|
Sign up to set email alerts
|

Blue Laser Imaging, Blue Light Imaging, and Linked Color Imaging for the Detection and Characterization of Colorectal Tumors

Abstract: A laser endoscopy system was developed in 2012. The system allows blue laser imaging (BLI), BLI-bright, and linked color imaging (LCI) to be performed as modes of narrow-band light observation; these modes have been reported to be useful for tumor detection and characterization. Furthermore, an innovative endoscopy system using four-light emitting diode (LED) multilight technology was released in 2016 to 2017 in some areas in which laser endoscopes have not been approved for use, including the United States an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 28 publications
0
48
0
2
Order By: Relevance
“…Regarding findings of NBI or BLI, SSL was diagnosed based on the presence of either crypts opening and dilated vessels, according to previous reports. 9,11 Lesions showing irregular vessel pattern were excluded due to the possibility of dysplasia. Among all lesions, the detail location and the distance from the anal verge were recorded at CSP for follow-up colonoscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding findings of NBI or BLI, SSL was diagnosed based on the presence of either crypts opening and dilated vessels, according to previous reports. 9,11 Lesions showing irregular vessel pattern were excluded due to the possibility of dysplasia. Among all lesions, the detail location and the distance from the anal verge were recorded at CSP for follow-up colonoscopy.…”
Section: Methodsmentioning
confidence: 99%
“…2,6,7 Operators have to differentiate benign lesions from cancerous lesions by white light image (WLI) and magnifying narrow-band imaging (NBI) or blue laser imaging (BLI). 2,8,9 Additionally, our previous study showed that the rate of local recurrence after CSP for polyps !10 mm was higher than that for polyps <10 mm. 10 Thus, CSP is not regularly recommended for neoplastic lesions !10 mm.…”
Section: Introductionmentioning
confidence: 98%
“…Multi‐laser imaging endoscopic system (Fujifilm Co., Tokyo, Japan) enables BLI, BLI‐bright, and LCI via narrow‐band light observation with a light source comprising two lasers with wavelengths of 410 and 450 nm …”
Section: Iee For Diagnosis Of Kyoto Classification Of Gastritismentioning
confidence: 99%
“…Multi-laser imaging endoscopic system (Fujifilm Co., Tokyo, Japan) enables BLI, BLI-bright, and LCI via narrow-band light observation with a light source comprising two lasers with wavelengths of 410 and 450 nm. 49,50 Blue laser imaging is a high-intensity contrast imaging that allows superior visualization of microvascular and microsurface patterns similar to NBI. BLI-bright is a brighter BLI to illuminate a wide lumen.…”
Section: Bli and Lcimentioning
confidence: 99%
“…BLI intensifies the blue light emission in the range of 410 nm, which enhances the visualization of the vessels and the mucosa. Alternatively, LCI accentuates color contrast by decreasing the intensity of blue-light and emphasizing red-light, providing better delineation and detection of lesions and inflammation [13,14].…”
Section: Introductionmentioning
confidence: 99%